Peran Artificial Intelligence (AI) dalam Peningkatan IT Governance: Kajian Literatur - Zulkarnain Zulkarnain; Jesselyn Jesselyn; Hansvirgo Hansvirgo; Fendy Gunawan; Sandy Alferro Dion (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Amidst the rapid advancement of artificial intelligence (AI), the need for effective integration within IT Governance becomes increasingly vital. In this context, the research background highlights the complexity and dynamics hindering the efficacy of IT Governance, while AI holds promise as a solution to these challenges. This study investigates the role of AI in enhancing IT Governance. The research aim is to explore the impact of AI on improving the effectiveness and efficiency of IT Governance through a literature review method. This method will gather and analyze relevant literature sources to gain a comprehensive understanding of AI's role in IT Governance. The findings encompass AI's potential in enhancing decision-making, proactive risk management, process automation, and user satisfaction. However, challenges such as data privacy and organizational cultural changes are also identified. The research implications underscore the need for a planned approach and ongoing evaluation in adopting AI to ensure successful implementation while managing associated risks.